The Meaning of The Verb 'Destroy' in the Balinese Language: A Natural Semantic Meta Language Approach - Swarniti, Ni Wayan (Humanis; Vol 25 No 3 (2021)DO - 10.24843/JH.2021.v25.i03.p05, 2021)
This research focused on the discussion about the analysis of the lexicon of the verb 'destroy' in the Balinese language. The data of this research are taken from some verbs in one meaning field with the verb 'destroy' which is found in the Balinese language. After the data collected, the data are analyzed based on the entities, the tools the manners which are related to the lexicons of the verb 'destroy'. Then, the findings of the research are presented descriptively. Based on the analysis, the lexicons in the Balinese language which have the same meaning field with the verb 'destroy' are Ngencakin, Ngremukin, Nguwugang, Menyahin, Nglidekin, Ngededekang, Ngeregreg, Nyakcakin, Nyetset, Mesbes, Ngincuk, and Ngenyagin. They are in the same meaning field but has different meaning based on the context of usage.